DIFFICULTIES IN TREATMENT OF BORDERLINE PERSONALITY DISORDER (BPD) – A REVIEW OF VARIOUS FORMS OF THERAPY AND PHARMACOLOGICAL METHODS - Marta Koneczna; Franciszek Szweda; Tomasz Poczwardowski; Adrianna Kaczmarek; Katarzyna Anna Kowalska; Jakub Tomasz Latos; Marcin Chwalczuk; Oliwia Grygorcewicz; Karolina Alicja Krystyniak; Kinga Augustyniak (International Journal of Innovative Technologies in Social Science, 2026)
Objective: The primary objective of this comprehensive review is to systematically evaluate and synthesize the latest scientific knowledge regarding the pathophysiology, diagnostic complexities, and the clinical effectiveness of various therapeutic interventions for borderline personality disorder (BPD).Methods: A narrative literature review methodology was employed, involving a rigorous search of leading scientific databases, including PubMed, Scopus, Web of Science, and Google Scholar. The selection process prioritized randomized clinical trials, extensive meta-analyses, and current treatment guidelines, with a particular emphasis on peer-reviewed publications from the last decade to ensure the utmost relevance.Findings: A review of the literature indicates that integrated evidence-based psychotherapy, particularly dialectical behavior therapy (DBT) and mentalization-based treatment (MBT), remains the gold standard for treating BPD. Furthermore, intensive short-term forms (5–6 months) have been shown to be more clinically effective than traditional long-term programs. Pharmacotherapy plays exclusively a supportive role and is utilized for the temporary relief of acute symptoms. Second-generation antipsychotics (SGAs) are highly effective in mitigating suicidal behavior in severe cases of BPD. New biological interventions, such as intravenous ketamine infusions or the modulation of the newly studied gut-brain axis, represent highly promising areas of future research.Conclusions: Effective treatment of BPD requires a highly personalized, holistic approach, with psychotherapy serving as its undeniable foundation. Pharmacotherapy must be introduced with extreme caution, placing particular emphasis on the absolute avoidance of polypharmacy.